The Scarcity Slot Excavating Histories of Food Security in Ghana - Logan, Amanda L. (University of California Press, 2020)
The Scarcity Slot is the first book to critically examine food security in Africa's deep past. Amanda L. Logan argues that African foodways have been viewed through the lens of "the scarcity slot," a kind of othering based on presumed differences in resources. Weaving together archaeological, historical, and environmental data with food ethnography, she advances a new approach to building long-term histories of food security on the continent in order to combat these stereotypes. Focusing on a case study in Banda, Ghana that spans the past six centuries, The Scarcity Slot reveals that people thrived during a severe, centuries-long drought just as Europeans arrived on the coast, with a major decline in food security emerging only recently. This narrative radically challenges how we think about African foodways in the past, with major implications for the future. "This book offers a pathbreaking archaeological ethnography of food in a region of West Africa that has experienced some of the most cataclysmic sociopolitical upheavals the world has ever seen. Amanda Logan dismantles the dominant narrative that Columbian Exchange crop introductions rescued a continent long shaped by hunger. This brilliant study elevates archaeology's contributions to African food history and food insecurity studies." JUDITH CARNEY, author of In the Shadow of Slavery: Africa's Botanical Legacy in the Atlantic World "The Scarcity Slot is an accessible, empirically grounded history demonstrating for students of Africa's futures the urgent need to understand her pasts." KATHRYN M. DE LUNA, Provost's Distinguished Associate Professor, Georgetown University "A radical shift from the old ways of doing the archaeology of diet, this book breaks ground for a new food archaeology. A truly innovative and exciting work and a convincing antidote to the popular image of Africa as a continent of famine." RICHARD WILK, Distinguished Professor and Provost's Professor Emeritus of Anthropology, Indiana University